Dibromohydantoin: A Convenient Brominating Reagent for 1, 4, 5, 8‐Naphthalenetetracarboxylic Dianhydride. Issue 9 (14th June 2013) - Sasikumar, M.; Suseela, Y. V.; Govindaraju, T.
Abstract An efficient and economical reagent for the bromination of 1, 4, 5, 8‐naphthalenetetracarboxylic dianhydride under mild reaction conditions is reported. 1, 4, 5, 8‐Naphthalenetetracarboxylic dianhydride was smoothly brominated by treatment with 5, 5‐dimethyl‐1, 3‐dibromohydantoin (DBH) in concentrated H2SO4 as a solvent under ambient conditions. Mono‐, di‐, and tetrabrominated products were obtained in good‐to‐excellent yield by varying the equivalents of brominating reagent used, and the products were purified by crystallization. The mild reaction conditions and simple workup procedure make this method a practical and commercially viable route for the synthesis of pure mono‐, di‐, and tetrabrominated 1, 4, 5, 8‐naphthalenetetracarboxylic dianhydrides. Condensation of these dianhydrides with n‐octylamine gives the corresponding imide (N, N′) substituted mono‐, di‐, and tetrabromonaphthalene diimides, which are versatile precursors for the synthesis of core‐functionalized naphthalene diimides. Toluene as a solvent significantly improves the efficiency of nucleophilic core substitution of these bromonaphthalene diimides with n‐octylamine to afford core‐substituted mono‐, di‐, and tetra‐(n‐octylamino)‐naphthalene diimides. The core substitution reactions are clean, without any side products, and give excellent yields. The UV/vis absorbance and fluorescence properties of the core functionalized naphthalene diimides were studied and found to be dependent on the number of core substituents.